LOSS PROCESSES IN THE CONCEPTS OF DEPTH PSYCHOLOGY - Komar, Tetiana; Bessarabа Olena (Personality and environmental issues, 2024)
The article presents a theoretical study of the problem of grieving as a multidimensional process that reveals the experiences of an individual in the event of loss of significant objects, such as loved ones, health or social status. For theoretical consideration, the author proposes to consider classical and modern models of grief, within the framework of a structural approach that defines grief in five successive stages (emotional reactions to loss): shock, denial, anger, bargaining, depression and acceptance. Attention is focused on the key tasks of grieving, including awareness of loss, integration of emotional experience, adaptation to changes and restoration of life prospects. The factors that influence the intensity and duration of the process, including individual characteristics, social support and the nature of the loss, are analysed. The differences between normative and complicated grieving, which require different approaches to psychological support, are identified. Particular attention is paid to the role of social ties and support in reducing the emotional burden of grieving. The importance of professional psychological assistance in cases of complicated grieving is emphasised. The necessity of integrating the experience of loss into the life history of a person as a key stage in overcoming the consequences of grief is substantiated. Recommendations for optimising psychological support for bereaved persons are proposed. It is concluded that an individual approach to support is important, considering the specifics of emotional response and life circumstances. A brief overview of foreign grief theories is provided. The phenomenon of grief as a natural reaction to loss is considered. T. Komar's point of view is a synthesis of relational theories in a broad sense, and is also based on attachment theory, modern research on the loss of a loved one, and personality development theory. The article pays special attention to the psychological features of normal and prolonged grief.